Heat dissipation material, heat dissipation component, electrostatic chuck, and method for producing heat dissipation
A Mo-Ti alloyed heat dissipation material with controlled Ti content and alloying ratio addresses the thermal expansion and peeling issues of conventional materials, ensuring effective heat dissipation and structural integrity in semiconductor manufacturing.
Patent Information
- Application Number
- JP2024059528
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-05
- Filing Date
- 2024-04-02
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional materials for electrostatic chucks used in semiconductor manufacturing, such as aluminum alloys, fail to maintain heat resistance and mechanical integrity under high heat input conditions, leading to thermal expansion mismatches and potential peeling or cracking of ceramic layers.
A heat dissipation material composed of a Mo phase and Ti phase, with Ti content between 3 to 50 atomic% and Mo as the remainder, providing high thermal conductivity, appropriate linear expansion coefficient, and controlled alloying ratio to ensure high relative density, preventing thermal stress-induced damage.
The material effectively dissipates heat and maintains structural integrity under high heat input, preventing peeling or cracking of ceramic layers and ensuring reliable operation of electrostatic chucks in semiconductor processing.
Smart Images

Figure 2024174805000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat dissipation material that can be suitably used particularly in processing steps with large heat input, a heat dissipation component including the heat dissipation material, an electrostatic chuck, and a method for producing the heat dissipation material. [Background technology]
[0002] Generally, in the manufacture of semiconductor devices, a thin film formation process and an etching process are repeatedly performed on a silicon wafer, thereby forming fine wiring and semiconductor elements. An electrostatic chuck is used to fix the wafer during the etching process. Specifically, the wafer is placed on a ceramic layer formed of ceramics (e.g., Al2O3, Y2O3, etc.) and fixed by electrostatic force. During the etching process, the wafer is heated by the influence of plasma, etc. For this reason, a base plate serving as a heat dissipation material is bonded under the ceramic layer to cool the wafer during the etching process.
[0003] Patent Document 1 discloses an electrostatic chuck in which the material of the base plate is aluminum or an aluminum alloy. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2017-103389 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in recent years, the integration density of semiconductors has increased, and the heat input during etching has become greater.
[0006] The present invention has been made in consideration of the above problems, and has an object to provide a heat dissipation material, a heat dissipation component, an electrostatic chuck including the heat dissipation component, and a method for manufacturing the heat dissipation material, which are suitable for use in processing steps in which a large heat input is applied. [Means for solving the problem]
[0007] The above object of the present invention can be achieved by the following configuration [1] relating to a heat dissipation material.
[0008] [1] Mo and Ti phases coexist, Contains 3 atomic % or more and 50 atomic % or less of Ti, A heat dissipation material, the balance being Mo.
[0009] Further, preferred embodiments of the present invention relating to the heat dissipation material relate to the following [2] and [3].
[0010] [2] The heat dissipation material according to [1], characterized in that, when the proportion of the Mo phase in the heat dissipation material measured by an X-ray diffraction method is defined as [Mo phase] in atomic %, and the concentration of all the Mo contained in the heat dissipation material is defined as [total Mo] in atomic %, the alloying ratio A represented by the following formula (1) is 15% or more and 80% or less. Formula (1): A = (1 - [Mo phase] / [total Mo]) x 100
[0011] [3] A heat dissipation material for use in an electrostatic chuck having a base plate, a ceramic layer provided on the base plate, and an electrode that generates static electricity on a surface of the ceramic layer, characterized in that the heat dissipation material according to [1] or [2] is used as a material for the base plate.
[0012] The above object of the present invention is achieved by the following configuration [4] relating to a heat dissipation component.
[0013] [4] A heat dissipation component comprising the heat dissipation material according to [1] or [2].
[0014] The above object of the present invention can be achieved by the following configuration [5] relating to an electrostatic chuck.
[0015] [5] An electrostatic chuck comprising: a base plate made of the heat dissipation component described in [4]; a ceramic layer provided on the base plate; and an electrode for generating static electricity on a surface of the ceramic layer.
[0016] The above object of the present invention is achieved by the following configuration [6] relating to a method for producing a heat dissipating material.
[0017] [6] A method for producing the heat dissipating material according to any one of [1] to [3], A mixing step of mixing a powder containing Mo and a powder containing Ti to obtain a mixture; and a sintering step of sintering the mixture. Effect of the Invention
[0018] According to the present invention, it is possible to provide a heat dissipation material that is suitable for use in a processing step in which a large heat input is applied, a heat dissipation component, an electrostatic chuck including the heat dissipation component, and a method for manufacturing the heat dissipation material. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a photograph, taken by a scanning electron microscope, of the structure of the heat dissipation material according to this embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view illustrating an example of an electrostatic chuck according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a graph showing the measurement results of the examples and comparative examples, with the thermal conductivity on the vertical axis and the linear expansion coefficient on the horizontal axis. [Figure 4] FIG. 4 is a graph showing the relationship between the relative density and the alloying ratio, with the vertical axis representing the relative density and the horizontal axis representing the alloying ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present inventors have conducted extensive research into materials for heat dissipation components that can be used in processing steps involving large heat input.
[0021] As mentioned above, the recent trend towards higher integration of semiconductors has resulted in greater heat input during etching. However, aluminum alloys, which have traditionally been used as base plate materials, have poor heat resistance, and heat treatment (aging treatment) during the manufacturing stage of aluminum alloys is carried out at temperatures up to about 200°C. Therefore, if the temperature of the base plate exceeds 200°C during the etching process, the material properties of the aluminum alloy cannot be maintained.
[0022] In addition, when a heat dissipation component is used in a process with a large heat input, the thermal expansion of the heat dissipation component has a large effect, and the size change rate between the heat dissipation component and the surrounding material may differ significantly. As a result, distortion occurs between the heat dissipation component and the surrounding material, and this distortion may cause the surrounding material to peel off or crack.
[0023] Furthermore, in order to apply heat dissipation components to processing steps that involve large heat input, they need to exhibit high heat dissipation properties.
[0024] That is, in order to apply a heat dissipation component to a process with a large heat input, it is important that the heat dissipation component has high heat resistance, an appropriate thermal expansion coefficient, and a high thermal conductivity. The present inventors have found that a heat dissipation component having desired characteristics can be obtained by using a material in which a Mo phase and a Ti phase coexist and the Ti content is appropriately controlled as a heat dissipation component. Furthermore, the present inventors have found that a good relative density can be obtained and a highly reliable heat dissipation material can be manufactured by controlling the alloying ratio of Mo and Ti within an appropriate range. The present invention has been made based on these findings.
[0025] Hereinafter, embodiments of the heat dissipation material for achieving high heat resistance, an appropriate linear expansion coefficient, and high thermal conductivity will be described in detail.
[0026] [Heat dissipation material] Among aluminum alloys, the tensile strength of 2000 series aluminum alloys, which are said to have high heat resistance, drops to 200 MPa at a temperature of 200°C (Katsumi Koyama, "High-strength, heat-resistant aluminum alloys," Furukawa-Sky Review, No. 6, 2010, p. 13, Figure 7). On the other hand, Mo is a high-melting-point metal with a melting point of 2623°C, and has extremely excellent heat resistance at temperatures of about 200°C. Specifically, the tensile strength of Mo is 550 MPa or more at 200°C (Takashi Murakami et al., "Molybdenum and Molybdenum Alloys," Journal of the Japan Welding Society, Vol. 57 (1988), No. 4, p. 293, Figure 2).
[0027] The heat dissipation material according to this embodiment is mainly composed of Mo, and therefore can significantly improve heat resistance. Mo is one of the pure metals with high thermal conductivity, and has a thermal conductivity more than twice that of iron and more than eight times that of titanium. Therefore, by using Mo as the main component of the heat dissipation material, it is possible to exhibit high heat dissipation properties.
[0028] The inventors also discovered that, in order to obtain a heat dissipating material having a particularly desired linear expansion coefficient, it is effective to allow a Mo phase and a Ti phase to coexist, rather than completely dissolving Ti in Mo, and more specifically, Ti has a larger linear expansion coefficient than Mo, and the linear expansion coefficient of the resulting alloy can be made closer to that of the material of the ceramic layer. However, if the Ti phase is not dispersed, the effect of adding Ti is weakened, and the linear expansion coefficient of the heat dissipating material approaches that of Mo.
[0029] As will be described in detail later, the heat dissipation material according to this embodiment is a sintered body obtained by mixing and sintering Mo powder and Ti powder, and more specifically, it is a sintered composite having a structure in which a Mo phase (body-centered cubic structure) and a Ti phase (hexagonal close-packed structure or body-centered cubic structure) coexist. This sintered composite has characteristics such as the inclusion of pores, and therefore it can be confirmed that it is a sintered body by observing the structure.
[0030] FIG. 1 is a drawing substitute photograph of the structure of the heat dissipation material according to the invention example No. 3, which will be described later, taken by a scanning electron microscope. As shown in FIG. 1, the heat dissipation material according to this embodiment has a black Ti phase 2 dispersed in a Mo phase 1, which is the main component. In this manner, this embodiment shows that a metal / metal composite material is formed. In addition, since this Ti phase 2 has the effect of increasing the linear expansion coefficient, by adjusting the Ti content, a heat dissipation material for heat dissipation parts that is suitable for use in a process in which a large heat input is applied can be obtained.
[0031] The contents of the components contained in the heat dissipation material in this embodiment will be described below.
[0032] (Ti: 3 atomic% or more and 50 atomic% or less) If the Ti content in the heat dissipating material is less than 3 atomic %, the effect of increasing the linear expansion coefficient of the heat dissipating material cannot be sufficiently obtained, and there is a risk that the ceramic layer (Al2O3 layer or Y2O3 layer, etc.) will peel off from the base plate or the ceramic layer will crack. Therefore, the Ti content in the heat dissipating material is set to 3 atomic % or more, preferably 4 atomic % or more, and more preferably 8 atomic % or more. On the other hand, if the Ti content in the heat dissipating material exceeds 50 atomic %, the thermal conductivity decreases and the required properties of the heat dissipating material cannot be obtained. Therefore, the Ti content in the heat dissipating material is set to 50 atomic % or less, preferably 45 atomic % or less, and more preferably 35 atomic % or less. In this way, by appropriately adjusting the Ti content in the heat dissipation material, it is possible to match the linear expansion coefficient to that of the ceramic layer (Al2O3 layer, Y2O3 layer, etc.), which makes it possible to prevent the ceramic layer (Al2O3 layer, Y2O3 layer, etc.) from peeling off from the base plate and to obtain excellent heat dissipation properties.
[0033] In this specification, when the proportions of Ti and Mo in the heat dissipation material are expressed in atomic %, the proportions of Ti atoms and Mo atoms are expressed in atomic % when the total of Ti atoms and Mo atoms in the heat dissipation material is 100 atomic %.
[0034] (Remainder: Mo) The heat dissipation material according to this embodiment contains Ti in the above range, with the remainder being Mo. Therefore, it is possible to obtain excellent heat resistance, as well as properties that combine high thermal conductivity and an appropriate linear expansion coefficient.
[0035] The heat dissipation material according to this embodiment does not contain Cu. If Cu is present in the chamber during the etching process, the chamber may be contaminated with Cu, which may affect the wiring structure. Therefore, the heat dissipation material according to this embodiment that does not contain Cu can be particularly preferably used in the etching process.
[0036] The heat dissipation material according to this embodiment may contain various impurities within a range that does not impair the effects of the present invention. Examples of impurities include oxygen, nitrogen, carbon, etc. derived from the powder raw material. In addition, Fe, Si, Mn, Mg, Cl, Al, V, Mn, Ni, Nb, etc. may also be contained. With regard to these impurities, it is considered empirically preferable to suppress oxygen to 3 mass% or less and other elements to 0.3 mass% or less. The above impurity contents are expressed in mass % when the total amount of Mo content and Ti content in the heat dissipation material according to this embodiment is taken as 100 mass %. Furthermore, so long as these elements are within the above-mentioned numerical ranges, the effects of this embodiment are not hindered even if they are intentionally added, not just when they are contained as unavoidable impurities.
[0037] The present inventors have found that by controlling the alloying ratio of Mo and Ti within an appropriate range, it is possible to obtain a good relative density in addition to excellent thermal conductivity and linear expansion coefficient. The alloying ratio of Mo and Ti will be described in more detail below.
[0038] <Alloying rate A: 15% or more and 80% or less> In the mixed powder of pure Mo powder and pure Ti powder, atomic diffusion occurs during the sintering stage, forming an alloyed region between Mo and Ti. The inventors have found that this alloyed region has a lower hot deformation resistance than pure Mo alone, and that the sintering is promoted as the alloying rate increases, improving the relative density. In other words, when a heat dissipation part containing a heat dissipation material with a low relative density is used for a base plate, there is a concern that the coolant for cooling the base plate may leak, or that cracks or breakage may be promoted due to thermal stress or mechanical stress associated with repeated use of the base plate. Therefore, obtaining a heat dissipation material having a good relative density leads to the production of a highly reliable base plate. In this specification, the alloying ratio is defined as the ratio of Mo consumed by alloying to the total Mo contained in the heat dissipation material.
[0039] The method for measuring the alloying ratio is explained below. First, the heat dissipation material after sintering is measured by X-ray diffraction (XRD). Next, the spectrum obtained by XRD is analyzed by whole powder pattern fitting (WPPF) to determine the Mo phase, Mo x Ti y The atomic fractions (atomic %) of the Ti phase and the Ti phase are then determined. Using these values, the alloying ratio can be calculated according to the formula (1) described below.
[0040] In this embodiment, a heat dissipating material having good relative density can be obtained by defining the alloying ratio A represented by the following formula (1). In the following formula (1), the term "Mo phase" refers to the proportion of the Mo phase in the heat dissipating material, as determined by X-ray diffraction, expressed in atomic %, and the term "total Mo" refers to the concentration of all Mo contained in the heat dissipating material, expressed in atomic %.
[0041] The Mo concentration in the heat dissipating material is the ratio of Mo atoms in atomic percent when the total of Ti atoms and Mo atoms in the heat dissipating material is taken as 100 atomic percent. The ratio of the Mo phase in the heat dissipating material is the ratio of the Mo phase, Mo x Ti y This is the ratio of Mo atoms constituting the Mo phase, expressed in atomic %, when all atoms constituting the Mo phase and Ti phase are taken as 100 atomic %. More specifically, [Mo phase] is the Mo phase obtained by the above-mentioned full pattern fitting method, Mo x Ti y The mass fraction of the Mo phase in the mass fractions of the Mo phase and the Ti phase (total of 100 mass%) can be calculated by the following formula (2). However, in the following formula (1), the alloying ratio A calculated using atomic % is the same value as the alloying ratio calculated using mass % instead of atomic %.
[0042] In addition, as will be described in detail later, the heat dissipating material can be manufactured by mixing a powder containing Mo with a powder containing Ti to prepare a mixture, and then sintering this mixture. For this reason, the concentrations at the time of mixing Ti powder and Mo powder generally become the Ti and Mo concentrations in the heat dissipating material after sintering. Therefore, if it is confirmed that there is only a difference of an error between the concentrations at the time of mixing and the concentrations in the heat dissipating material after sintering, the Mo concentration at the time of powder mixing can be used as the Mo concentration ([total Mo]) in the heat dissipating material.
[0043] Formula (1): A = (1 - [Mo phase] / [total Mo]) x 100 Equation (2): [Mo phase] = ({Mo phase} / atomic weight of Mo) / ([Mo content] / atomic weight of Mo + [Ti content] / atomic weight of Ti) In the above formula (2), the "Mo phase" is a value expressed in atomic % of the proportion of the Mo phase in the heat dissipating material, as determined by X-ray diffraction. {Mo phase} is the mass fraction of the Mo phase obtained by XRD. x Ti yThis is the ratio of the Mo phase expressed in mass % when the total of the Mo phase and the Ti phase is taken as 100 mass %. [Mo content] is the total Mo content contained in the heat dissipating material expressed as mass %. [Ti content] is the total Ti content contained in the heat dissipating material expressed as mass %.
[0044] When the alloying ratio A calculated by the above formula (1) is 15% or more, a higher relative density can be obtained, and the occurrence of cracks, breakage, etc. due to the load of thermal stress or mechanical stress can be suppressed. Therefore, the alloying ratio A calculated by the above formula (1) is preferably 15% or more, more preferably 30% or more, and even more preferably 40% or more. In addition, when the alloying ratio A calculated by the above formula (1) is 80% or less, the temperature required for sintering can be prevented from becoming too high or the time can be prevented from becoming too long, and the wear of the sintering mold can be suppressed and good productivity can be maintained. Therefore, the alloying ratio A calculated by the above formula (1) is preferably 80% or less, more preferably 70% or less, and even more preferably 60% or less. By controlling the alloying ratio to such a level, a heat dissipation material having a high relative density in addition to good thermal conductivity and linear expansion coefficient can be obtained. Furthermore, when a heat dissipation part containing such a heat dissipation material is used for a base plate, the performance and reliability of the base plate can be improved.
[0045] Here, examples of manufacturing conditions for heat dissipation materials having an alloying ratio in the above range will be described. The alloying ratio is due to atomic diffusion between Mo and Ti, and can be controlled by changing the temperature and time required for the process in the post-processing step in which a thermal load is applied, such as the sintering process or the bonding process performed as necessary. For example, the thermal load for sintering and bonding can be performed under conditions according to the equipment and powder characteristics, with a temperature of 800°C to 1400°C, a holding time of 5 minutes to 16 hours, and a pressure of 2 MPa to 50 MPa as a guideline.
[0046] The relative density will be described below. In this embodiment, by controlling the alloying ratio A within an appropriate range, a good relative density can be obtained, and as a result, a highly reliable heat dissipation material can be obtained. The relative density D is calculated by dividing the density d obtained by the underwater substitution method (Archimedes method) by the density d m The value of theoretical density d t That is, the relative density D can be expressed by the following formula (3).
[0047] Equation (3): D=(d m / d t ) x 100
[0048] In addition, the theoretical density d t can be calculated by the following formula (4).
[0049] Formula (4):d t =100 / ([Ti content] / [Ti specific gravity]+[Mo content] / [Mo specific gravity]) In the above formula (4), the Ti content is the amount of Ti contained in the heat dissipating material expressed in mass%, the Ti specific gravity is the amount of pure Ti, the Mo content is the amount of Mo contained in the heat dissipating material expressed in mass%, and the Mo specific gravity is the amount of pure Mo.
[0050] The relative density D is preferably 98% or more, more preferably 98.5% or more, even more preferably 99% or more, and even more preferably 99.5% or more. Furthermore, the relative density D is preferably 100.0% or more, more preferably 100.5% or more, and even more preferably 101.0% or more.
[0051] [Heat dissipation parts] The heat dissipation component according to this embodiment is obtained by machining the heat dissipation material (sintered composite) according to the embodiment described above, and has excellent heat resistance, as well as a large thermal conductivity and an appropriate linear expansion coefficient. Therefore, when this heat dissipation component is used, heat can be sufficiently dissipated in a processing process with a large heat input. In addition, since this heat dissipation component has an appropriate linear expansion coefficient, even if the influence of thermal expansion is large in a process with a large heat input, the size change rate of the surrounding material and the size change rate of the heat dissipation component are close to each other. Therefore, it is possible to suppress the occurrence of distortion between the heat dissipation component and the surrounding material, and to prevent peeling or cracking of the surrounding material.
[0052] [Electrostatic chuck] Fig. 2 is a schematic cross-sectional view showing an example of an electrostatic chuck according to an embodiment of the present invention. As shown in Fig. 2, an electrostatic chuck 10 includes a base plate 11 made of the above-mentioned heat dissipation component, a ceramic layer 12 provided on the base plate 11, and an electrode 14 for generating static electricity on a surface 12a of the ceramic layer 12. A coolant flow path 13 is provided inside the base plate 11. Note that an electrostatic chuck is a device that grips a member by utilizing the force of static electricity, and the electrostatic chuck can be applied to semiconductor manufacturing equipment, electrostatic robot hands, and the like.
[0053] There are various types of semiconductor manufacturing apparatuses, such as a polishing apparatus, a developing apparatus, an exposure apparatus, and an etching apparatus. For example, an etching apparatus has the electrostatic chuck 10 according to the present embodiment and a plasma generation / processing chamber in which the electrostatic chuck 10 is arranged. When the electrostatic chuck 10 according to the present embodiment is used in an etching apparatus, a silicon wafer (not shown) is placed on the electrostatic chuck 10 arranged in the plasma generation / processing chamber, and a voltage is applied to the electrode 14 to generate static electricity on the surface of the ceramic layer 12, thereby fixing the silicon wafer. Then, in a vacuum atmosphere, the wafer surface is etched by using plasma in the plasma generation / processing chamber. Since the plasma is high in temperature and the temperature rises during etching, the wafer is cooled by flowing a coolant through a coolant passage 13 formed in the base plate 11.
[0054] As described above, the heat input during etching has become large due to the recent high integration of semiconductors, so that the base plate is required to have high heat resistance. The heat dissipation material and heat dissipation member according to this embodiment are preferably used in a process in which a large heat input is applied. That is, by using the electrostatic chuck according to this embodiment, the silicon wafer can be effectively cooled even in a high-temperature etching process corresponding to the miniaturization and high integration of semiconductor devices. In addition, since the heat dissipation parts have an appropriate linear expansion coefficient, it is possible to suppress the occurrence of distortion between the ceramic layer and the base plate even in the above-mentioned etching process, and it is possible to prevent the occurrence of peeling or cracking in the ceramic layer. Furthermore, since Cu is not contained in the heat dissipation parts constituting the base plate, it is possible to prevent the inside of the etching chamber from being contaminated even when used in the etching process. Therefore, the electrostatic chuck according to this embodiment is particularly preferably used in an etching device.
[0055] [Method of manufacturing heat dissipation materials] The method for producing a heat dissipation material according to this embodiment is a method for producing the above-mentioned heat dissipation material, and includes a mixing step of mixing a powder containing Mo and a powder containing Ti to obtain a mixture, and a sintering step of sintering the mixture.
[0056] The sintering method in the sintering step is not particularly limited, and for example, a spark plasma sintering (SPS) method, a hot pressing method, a hot isostatic pressing (HIP) method, etc. can be used. In addition, the sintering conditions in the sintering step are also not particularly limited, and the sintering can be performed under conditions according to the characteristics of the equipment and the characteristics of the powder, for example, the sintering temperature is about 800°C to 1600°C, the sintering holding time is 5 minutes to 3 hours, and the pressure is 10 MPa to 50 MPa.
[0057] In this specification, the powder containing Mo and the powder containing Ti used as the heat dissipation material include those containing oxygen, nitrogen, carbon, etc. derived from the powder raw material as impurities. For example, an alloy powder may be used as the heat dissipation material as long as the effect of the present invention is not impaired.
[0058] Also, a heat dissipation part such as a base plate can be manufactured by performing external processing and groove processing on the material sintered by the SPS method or the hot pressing method, or the material sintered by the HIP method and then forged. Furthermore, a ceramic layer is formed on the upper surface of the obtained heat dissipation part by diffusion bonding, and then finishing processing is performed by cutting, thereby manufacturing an electrostatic chuck in which the base plate and the ceramic layer are bonded. In addition to the diffusion bonding, methods for bonding the base plate and the ceramic include brazing, bonding with an adhesive, and fixing with screws.
[0059] The heat dissipation material, heat dissipation component, electrostatic chuck, and method for manufacturing a heat dissipation material according to the present invention are not limited to the above-described embodiments, and can be modified as desired without departing from the gist of the present invention. In the above-mentioned embodiment, the heat dissipation component is used as a base plate of an electrostatic chuck used during etching in a semiconductor manufacturing device, but the present invention is not limited thereto, and the heat dissipation material and heat dissipation component of the present invention can be used as any heat dissipation material and heat dissipation component. Since the heat dissipation material of the present invention has the above-mentioned characteristics, it is suitably used as a material for a heat dissipation component used in a processing step in which a particularly large heat input is applied. EXAMPLES
[0060] The heat dissipation material according to the present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples, and can be modified within the scope of the present invention, and all of these are included in the technical scope of the present invention. In addition, the heat dissipation material and its manufacturing conditions described below are examples, and the present invention is not limited to the following examples.
[0061] [First Example] (Manufacture of heat dissipating materials) First, Mo powder and Ti powder were mixed to obtain mixtures so as to form Mo-Ti sintered composites with various compositions. The mixtures obtained were then sintered by a powder sintering method using a hot press method or an SPS method to produce sintered bodies of invention examples No. 1 to No. 4. In addition, a sintered body was produced by sintering only Mo powder, which was used as comparative example No. 1. Comparative examples No. 2, No. 3, and No. 4 were respectively made of known alumina (Al2O3), pure aluminum, and 2024-T6 alloy, a 2000 series aluminum alloy known as duralumin. Inventive Example No. 1, Inventive Example No. 2, and Comparative Example No. 1 were sintered by the hot press method, and Inventive Example No. 3 and Inventive Example No. 4 were sintered by the SPS method.
[0062] (Component Analysis) The components of the invention examples No. 1 to No. 4 were analyzed by inductively coupled plasma (ICP) emission spectrometry. The analysis results of the components of the heat dissipation materials in the invention examples and the materials of the sintered bodies in the comparative examples are shown in Tables 1 and 2 below. Note that the compositions shown in Table 1 are expressed in atomic % for the proportions of Ti atoms and Mo atoms when the total of Ti atoms and Mo atoms is 100 atomic %.
[0063] (Measurement of thermal conductivity) For the obtained sintered body, the specific heat at room temperature was measured by a differential scanning calorimetry (DSC) and the thermal diffusivity was measured by a flash method, and the thermal conductivity was calculated from these values.
[0064] (Measurement of linear expansion coefficient) For the obtained sintered body, the linear expansion coefficient at 40° C. to 400° C. was measured by thermomechanical analysis (TMA method).
[0065] (Observation of material structure) The obtained sintered body was mirror-polished, and the material structure was observed by taking a backscattered electron image using a scanning electron microscope.
[0066] The measurement results of the thermal conductivity and linear expansion coefficient are shown in Tables 1 and 2 below. The thermal conductivity and linear expansion coefficient of Al2O3 of Comparative Example No. 2 can be found on the KYOCERA Japan website ("Alumina Al2O3", [searched December 13, 2022], Internet<URL;https: / / www.kyocera.co.jp / prdct / fc / material-property / material / alumina / index.html> ) were used to cite the values for the material code "AO476O". For the thermal conductivity and linear expansion coefficient of pure Al in Comparative Example No. 3, the values were used to cite the values in "Metal Data Book" (edited by the Japan Institute of Metals, Maruzen, 2004,). For the thermal conductivity and linear expansion coefficient of Al alloy (2024-T6) in Comparative Example No. 4, the values were used to cite the values in "Aluminum Handbook", Japan Aluminum Association, 2007).
[0067] The thermal conductivity of pure Al shown in Table 2 below is measured at 200° C., and the linear expansion coefficient is measured at 20 to 400° C. The linear expansion coefficient of Al alloys shown in Table 2 below is measured at 20 to 300° C.
[0068] [Table 1]
[0069] [Table 2]
[0070] (Evaluation of Examples and Comparative Examples) FIG. 3 is a graph showing the measurement results of the invention examples and the comparative examples, with the thermal conductivity on the vertical axis and the linear expansion coefficient on the horizontal axis. The dotted line in the figure indicates the linear expansion coefficient of alumina. FIG. 1 is a micrograph of the structure of the invention example No. 3. As a result of observing the material structure of the invention examples No. 1 to No. 4, it was confirmed that the Mo phase and the Ti phase coexisted in all the invention examples, as in the micrograph shown in FIG. 1. Also, as shown in Tables 1 and 2 above, the linear expansion coefficients of the sintered bodies of the invention examples No. 1 to No. 4 were larger than that of the sintered body of the comparative example No. 1 that does not contain Ti, and were close to the linear expansion coefficient of Al2O3 used as a material for electrostatic chucks. In particular, the linear expansion coefficients of the sintered bodies of the invention examples No. 1 to No. 4 were very close to the linear expansion coefficient of alumina, which is the comparative example No. 2, compared to the conventional materials of the comparative examples No. 3 and 4. Furthermore, when comparing the sintered bodies of the invention examples Nos. 1 to 4, it was confirmed that the linear expansion coefficient increased with an increase in the Ti concentration in the sintered body, approaching the linear expansion coefficient of Al2O3.
[0071] From the above results, it was shown that when a heat dissipation component is manufactured using the sintered bodies of the invention examples No. 1 to 4, the obtained heat dissipation component has excellent heat dissipation properties. In addition, since the linear expansion coefficient is close to that of the ceramic layer made of alumina bonded to the heat dissipation component, it is possible to prevent the occurrence of cracks, peeling, etc. of the ceramic layer. Furthermore, the sintered bodies of the invention examples No. 1 to 4 are mainly composed of Mo and contain a predetermined amount of Ti, both of which are highly heat-resistant components, and therefore have high heat resistance. Furthermore, since the sintered bodies of the invention examples No. 1 to 4 do not contain Cu, when heat dissipation components made of these sintered bodies are used in the etching process of a semiconductor manufacturing device, contamination inside the chamber can be suppressed.
[0072] [Second Example] (Manufacture of heat dissipating materials) Pure Mo powder and pure Ti powder were mixed and sintered by a powder process using hot pressing and SPS to produce a Mo-Ti sintered body (heat dissipation material).
[0073] (Measurement of Ti powder concentration during mixing and Ti concentration in heat dissipation material after sintering) In addition to the manufacture of the above heat dissipation material, Mo powder and Ti powder were mixed in various ratios, and the concentration of Ti powder when Mo powder and Ti powder were mixed was calculated. In addition, the mixed mixture was sintered by a powder process using hot pressing and SPS to manufacture sintered test pieces. The Ti concentration of each test piece was then analyzed by inductively coupled plasma (ICP) atomic emission spectrometry and compared with the concentration of the above Ti powder. The calculation results of the concentration when mixed and the analysis results of the Ti concentration after sintering are shown in Table 3 below.
[0074] [Table 3]
[0075] As shown in Table 3, the concentration of Ti powder when Mo powder and Ti powder were mixed was compared with the analytical value of the Ti concentration in the sintered heat dissipation material, and only a slight difference was found, which is within the margin of error. Therefore, in this embodiment, the concentrations of Ti powder and Mo powder when mixed were regarded as the Ti concentration and Mo concentration in the sintered heat dissipation material.
[0076] (Calculation of relative density D and alloying ratio A) For the obtained Mo-Ti sintered body (heat dissipating material), the relative density D and the alloying ratio A were calculated. The relative density D can be calculated by the following formula (3).
[0077] Equation (3): D=(d m / d t ) x 100 However, d m is the density of the sintered body measured by the underwater displacement method, and d t is the theoretical density d calculated by the following formula (4) t It is.
[0078] Formula (4):d t =100 / ([Ti content] / [Ti specific gravity]+[Mo content] / [Mo specific gravity]) In the above formula (4), the Ti content is the Ti content contained in the heat dissipating material, and the Ti powder content in the raw powder is expressed in mass%. The Ti specific gravity is the value representing the specific gravity of pure Ti. The Mo content is the Mo content contained in the heat dissipating material, and the Mo powder content in the raw powder is expressed in mass%. The Mo specific gravity is the value representing the specific gravity of pure Mo. The specific gravity of pure Ti is 4.508, and the specific gravity of pure Mo is 10.222.
[0079] In order to calculate the alloying ratio A, the sintered body was measured by X-ray diffraction (XRD) and analyzed by the WPPF method using the spectrum with a 2θ angle of 20 to 140°. x Ti y The concentrations of the Ti phase and the Ti phase were measured. The conditions of the program used for the analysis by the WPPF method and the measurement conditions by XRD are shown below.
[0080] -Analysis conditions using the WPPF method Analysis program: JADE PRO (version 8) by Materials Data Inc. (MDI) Database:ICDD PDF-4+ XRD measurement conditions Micro X-ray diffraction equipment: Rigaku Corporation RINT-RAPIDII Collimator diameter: 300μm ω angle: 20~25°(2° / sec) φ angle: rotation (1° / sec)
[0081] The alloying ratio A was calculated using the following formula (1) from the content of the Mo phase in the sintered body and the concentration of all Mo contained in the sintered body ([Total Mo] (atomic %)) obtained by the above XRD analysis. In the following formulas (1) and (2), [Mo phase] is a value expressed in atomic % of the proportion of Mo atoms constituting the Mo phase in the sintered body, as specified by X-ray diffraction, and [Total Mo] is a value expressed in atomic % of the concentration of all Mo contained in the sintered body. Also, {Mo phase} is the mass fraction of the Mo phase obtained by XRD, and the Mo phase, Mo x Ti y The Mo content is a value expressed in mass% of the proportion of the Mo phase when the sum of the Mo phase and the Ti phase is taken as 100 mass%. The [Mo content] is a value expressed in mass% of the total content of Mo contained in the sintered body. The [Ti content] is a value expressed in mass% of the total content of Ti contained in the sintered body. As described above, the concentration of Mo powder in the raw material powder can be used as the concentration of Mo in the sintered body.
[0082] Formula (1): A = (1 - [Mo phase] / [total Mo]) x 100 Equation (2): [Mo phase] = ({Mo phase} / atomic weight of Mo) / ([Mo content] / atomic weight of Mo + [Ti content] / atomic weight of Ti)
[0083] (Measurement of thermal conductivity and linear expansion coefficient) The thermal conductivity and linear expansion coefficient were measured in the same manner as in Example 1. Various measurement results and calculation results for Examples 21 to 29 are shown in Table 4 below. Note that in Table 4 below, Example 21 corresponds to Example 4 in the above-mentioned Example 1, and Example 29 corresponds to Example 3 in the above-mentioned Example 1.
[0084] [Table 4]
[0085] (Evaluation of invention examples) FIG. 4 is a graph showing the relationship between relative density and alloying ratio, with the vertical axis representing the relative density and the horizontal axis representing the alloying ratio. As shown in FIG. 4, as the alloying ratio increases, the relative density value also increases, approaching 100%. Furthermore, in the invention examples in which the alloying ratio is 15-80%, as shown by the arrow in FIG. 4, a particularly good relative density was shown. Furthermore, in the range of the alloying ratio of 30% or more, the relative density became even higher, and a value close to or exceeding 100% could be obtained.
[0086] As shown in the first and second examples, a heat dissipation material in which a Mo phase and a Ti phase coexist can be obtained by controlling the Ti content within a predetermined range and further controlling the alloying ratio within an appropriate range, thereby making it possible to obtain a sound heat dissipation material that not only has excellent thermal conductivity and linear expansion coefficient but also has a high relative density. A base plate using the heat dissipation material obtained in this way has no risk of refrigerant leakage, and can suppress the occurrence of cracks and fractures that occur when thermal or mechanical stress is applied, thereby extending the life of the base plate and improving its reliability. [Explanation of symbols]
[0087] 1 Mo phase 2. Ti phase 10 Electrostatic Chuck 11 Base plate 13 Coolant flow path 12 Ceramic layer 14 electrodes
Claims
1. Mo phase and Ti phase coexist, Contains Ti at 3 atomic % or more and 50 atomic % or less, A heat dissipation material, the balance being Mo.
2. The heat dissipation material according to claim 1, characterized in that, when the proportion of the Mo phase in the heat dissipation material measured by an X-ray diffraction method is defined as [Mo phase] in atomic %, and the concentration of all the Mo contained in the heat dissipation material is defined as [total Mo] in atomic %, an alloying ratio A represented by the following formula (1) is 15% or more and 80% or less. Formula (1): A = (1 - [Mo phase] / [total Mo]) x 100
3. 1. A heat dissipation material for use in an electrostatic chuck having a base plate, a ceramic layer provided on the base plate, and an electrode for generating static electricity on a surface of the ceramic layer, comprising: The heat dissipation material according to claim 1 or 2, which is used as a material for the base plate.
4. A heat dissipation component comprising the heat dissipation material according to claim 1 or 2.
5. 5. An electrostatic chuck comprising: a base plate made of the heat dissipation component according to claim 4; a ceramic layer provided on the base plate; and an electrode for generating static electricity on a surface of the ceramic layer.
6. A method for producing the heat dissipation material according to claim 1 or 2, comprising the steps of: A mixing step of mixing a powder containing Mo and a powder containing Ti to obtain a mixture; and a sintering step of sintering the mixture.
Citation Information
Patent Citations
Vacuum sealing assembly
JP1982111943A
Ceramic joining part
JP2000335981A
Cooling unit member
JP2003229474A
Sputtering target for thin film deposition
JP2005029862A
Substrate loading table
JP2008103713A
